Evaluating the Reliability of Emergency Response Systems for Large-Scale Incident Operations - Jackson, Brian A. (RAND Corporation, 2010)
The ability to measure emergency preparedness is critical for policy analysis in homeland security. Yet it remains difficult to know how prepared a response system is to deal with large-scale incidents, whether it be a natural disaster, terrorist attack, or industrial or transportation accident. This volume describes a method, based on the concept of system reliability, for evaluating the preparedness of emergency response systems.